Sistem Akuntansi Penjualan Pada Toko Bangunan Impian Kaliwungu - Edy Siswanto; Haris Ihsanil Huda; Eko Siswanto (Universitas Sains dan Teknologi Komputer, 2020)
Kaliwungu Dream Building Shop is a business engaged in the sale of building materials and building-producing tools. This trading business sells various materials and tools for building buildings such as sand, cement, nails, paint, hammers and so on. The Dream Building Shop was founded by Mr. Zaenal, whose address is Jalan Raya Sekopek No. 10 Sarirejo Kaliwungu, Kendal Regency. Kaliwungu Dream Building Shop in recording sales transactions, purchases and reports - reports still use the manual method by writing them into a book, this method still requires time which is relatively old and prone to calculation errors, as a result you have to work 2 times or even many times to recalculate transactions that occur. Factors that are generally controlled are human errors that occur in cooking data and storing & maintaining paper-shaped documents, where this is very difficult to overcome. In addition, the process of searching for data or inventory is also less effective and efficient. also affect customers, even though performance according to the store is needed to satisfy customers.